Autoantibodies to harmonin and villin are diagnostic markers in children with IPEX syndrome. - Vito Lampasona; Laura Passerini; Federica Barzaghi; Carlo Lombardoni; Elena Bazzigaluppi; Cristina Brigatti; Rosa Bacchetta; Emanuele Bosi (PLoS ONE)
Autoantibodies to enterocyte antigens harmonin (75 kDa USH1C protein) and villin (actin-binding 95 kDa protein) are associated with the Immune dysregulation, Polyendocrinopathy, Enteropathy, X-linked (IPEX) syndrome. In this study we evaluated the diagnostic value of harmonin and villin autoantibodies in IPEX and IPEX-like syndromes. Harmonin and villin autoantibodies were measured by a novel Luminescent-Immuno-Precipitation-System (LIPS) quantitative assay, in patients with IPEX, IPEX-like syndrome, Primary Immunodeficiencies (PID) with enteropathy, all diagnosed by sequencing of the FOXP3 gene, and in type 1 diabetes (T1D), celiac disease and healthy blood donors as control groups. Harmonin and villin autoantibodies were detected in 12 (92%) and 6 (46%) of 13 IPEX patients, and in none of the IPEX-like, PID, T1D, celiac patients, respectively. All IPEX patients, including one case with late and atypical clinical presentation, had either harmonin and/or villin autoantibodies and tested positive for enterocyte antibodies by indirect immunofluorescence. When measured in IPEX patients in remission after immunosuppressive therapy or hematopoietic stem cell transplantation, harmonin and villin autoantibodies became undetectable or persisted at low titers in all cases but one in whom harmonin autoantibodies remained constantly high. In one patient, a peak of harmonin antibodies paralleled a relapse phase of enteropathy. Our study demonstrates that harmonin and villin autoantibodies, measured by LIPS, are sensitive and specific markers of IPEX, differentiate IPEX, including atypical cases, from other early childhood disorders associated with enteropathy, and are useful for screening and clinical monitoring of affected children.